THEORETICAL AND PRACTICAL STATE OF THE PROBLEM OF SENDING STUDENTS TO TRAINING CENTERS FOR OLYMPIC AND PARALYMPIC SPORTS - Jamshid Abdumadjitovich Pulatov (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides information on the theoretical and practical state of the problem of sending students to training centers for Olympic and Paralympic sports, the psychophysiological approach, the analysis of the questionnaire, cooperation, the problem of self-esteem.